Synthesis of 5-Functionalized 1-(Hetero)Aryl-1,2-thiazine 1-Oxides through a CSIC Reaction Strategy - Chuchvera, Yaroslav O.; Korobka, Oleksandr P.; Horbatochkin, Yurii O.; Ostapchuk, Eugeniy N.; Popova, Maria V.; Shishkina, Svitlana V.; Volovenko, Yulian M.; Dobrydnev, Alexey V. (Synlett, 2025)
Herein, we report an efficient strategy for the synthesis of C5-functionalized 1-(hetero)aryl-1,2-thiazine 1-oxides (i.e., C5-functionalized six-membered endocyclic sulfoximines) based on the carbanion-mediated sulfonate (or sulfonamide) intermolecular coupling and intramolecular cyclization (CSIC) reaction. The starting compounds are readily available 2,2-disubstituted 3-bromopropanenitriles and imino(methyl)(hetero/aryl)-λ6-sulfanones, and the reaction is performed in a one-pot fashion. The method works well and provides previously unreported spirocyclic and S-heteroaryl-substituted 1,2-thiazine 1-oxides. These compounds are designed as multi-target small molecules and a preliminary in silico study indicates their good binding affinity to CLK4 and MAO B – the receptors associated with cancer and neurodegenerative diseases.
Keywords: sulfoximines; CSIC reaction; cyclization; alkylation; enamines